2020
DOI: 10.5946/ce.2019.209
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Oral Sulfate Solution and Polyethylene Glycol Plus Ascorbic Acid on the Efficacy of Bowel Preparation

Abstract: Background/Aims: The quality of bowel preparation is one of the quality indicators for colonoscopy. The aim of this study was to compare the efficacy of oral sulfate solution (OSS) and polyethylene glycol plus ascorbic acid (PEG-AA) for bowel preparation. Methods: The study involved 167 patients who underwent diagnostic colonoscopies. Inadequate bowel preparation was defined as any score of ≤1 in each colon section based on the Boston Bowel Preparation Scale. Multivariate logistic regression was used to compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…This discrepancy among results is probably due to the heterogeneous designs of the studies. Similar to our study, two previous studies that focused on bowel preparation quality and analyzed ADRs or PDRs did not find any significant differences among cleansing solutions [20,26]. The split-dose regimen was accepted most often in the 2L-PEG/Asc group (92%).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This discrepancy among results is probably due to the heterogeneous designs of the studies. Similar to our study, two previous studies that focused on bowel preparation quality and analyzed ADRs or PDRs did not find any significant differences among cleansing solutions [20,26]. The split-dose regimen was accepted most often in the 2L-PEG/Asc group (92%).…”
Section: Discussionsupporting
confidence: 88%
“…Many studies comparing quality of bowel preparation have already been published. There is a high degree of heterogeneity among the studies because of the different study designs, including different types of compared agents, administration, and evaluation scales [17][18][19][20][21][22][23][24][25][26]. The present study was a prospective, randomized, unicentric, and investigator-blinded study.…”
Section: Discussionmentioning
confidence: 99%
“…However, adequate bowel preparation is one of the most important factors associated with the optimal visualization of bowel mucosa and detection of polyps during colonoscopy [6,12]. Unsuccessful colonoscopy or failed colonoscopy, defined as a failure to intubate the cecum, can occur in 25-40% of the subjects with inadequate bowel preparation [13][14][15]. Inadequate bowel preparation is also as-sociated with a reduced adenoma detection rate (ADR), an increased in procedure time, an increased risk of colonoscopy associated complications and reduced surveillance intervals [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…6 However, it has been reported that the rate of inadequate bowel preparation in the patients undergoing colonoscopy in real-life clinical practice is 25%-30%. 7,8 In this issue of Clinical Endoscopy, Nam et al 9 compared the efficacy of OSS and PEG-AA and identified the patient characteristics that were favorable in certain formulations. Overall, 106 (63.5%) patients received OSS and 61 (36.5%) patients received PEG-AA.…”
mentioning
confidence: 99%
“…In this issue of Clinical Endoscopy , Nam et al [ 9 ] compared the efficacy of OSS and PEG-AA and identified the patient characteristics that were favorable in certain formulations. Overall, 106 (63.5%) patients received OSS and 61 (36.5%) patients received PEG-AA.…”
mentioning
confidence: 99%